Clinical, therapeutic and evolutionary characteristics of anti-MOG-associated disease in pediatric patients (Archives of Pediatrics of Uruguay, 2025)
Introduction: inflammatory Demyelinating Diseases include a broad spectrum of diseases involving the central nervous system. Among them, Myelin Oligodendrocyte Glycoprotein Antibody-Associated Disease (MOGAD) includes syndromes affecting both white and gray matter. MOGAD is identified through anti-MOG antibodies and is treated with immunotherapy, generally presenting a good prognosis in most cases, although some relapsing forms require prolonged treatment.Objectives: describe the clinical characteristics, treatments administered, and outcomes of a group of children diagnosed with MOGAD, treated at the Pediatric Neurology Service of the Centro Hospitalario Pereira Rossell between January 2022 and June 2024.Methodology: observational, descriptive, retrospective study based on the clinical records of 14 patients with MOGAD.Results: we included 14 patients (6 girls and 8 boys) aged 2 to 14 years, with a mean age of 8.7 years. The clinical phenotypes were: acute disseminated encephalomyelitis (n=1), extensive transverse myelitis (n=4), neuromyelitis optica spectrum (n=4), encephalitis (n=4), and monofocal neurological syndrome (n=1). All received intravenous methylprednisolone, which was the only treatment in 9 cases. Two patients additionally required plasmapheresis, one intravenous immunoglobulin (IVIG), and another plasmapheresis, IVIG, and rituximab. Four patients relapsed, three with optic neuritis. Two were treated with azathioprine and two with rituximab. One patient remains under immunosuppression due to the initial severity.Conclusions: MOGAD is a demyelinating disease with varied clinical phenotypes. It requires a high level of suspicion, with a specific and sensitive biomarker available. The response to treatment is generally good, with few relapses and a low rate of neurological sequelae.
Keywords: Myelin Oligodendrocyte Glycoprotein Antibody-Associated Disease; Child